2017
DOI: 10.1136/bmjopen-2017-019023
|View full text |Cite|
|
Sign up to set email alerts
|

Values and preferences of women living with HIV who are pregnant, postpartum or considering pregnancy on choice of antiretroviral therapy during pregnancy

Abstract: ObjectiveTo investigate women’s values and preferences regarding antiretroviral therapy (ART) during pregnancy to inform a BMJ Rapid Recommendation.SettingPrimary studies reporting patient-reported outcomes relevant to decision-making regarding ART in any clinical and geographical setting.ParticipantsWomen living with HIV who are pregnant, postpartum or considering pregnancy.Outcome measuresQuantitative measurements and qualitative descriptions of values and preferences in relation to ART during pregnancy. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
2
7
1
Order By: Relevance
“…In our review, the lack of reflexivity in the included studies meant that it was difficult to assess the extent to which the discussions around clinic attendance were shaped by the nature of the relationships between the field workers and the participants. Similar concerns have been found in other reviews of qualitative research from African settings (Lytvyn et al, 2017). However, despite the absence of statements on reflexivity in many studies, we noted that authors from sub-Saharan Africa were well represented in the identified papers.…”
Section: Discussionsupporting
confidence: 83%
“…In our review, the lack of reflexivity in the included studies meant that it was difficult to assess the extent to which the discussions around clinic attendance were shaped by the nature of the relationships between the field workers and the participants. Similar concerns have been found in other reviews of qualitative research from African settings (Lytvyn et al, 2017). However, despite the absence of statements on reflexivity in many studies, we noted that authors from sub-Saharan Africa were well represented in the identified papers.…”
Section: Discussionsupporting
confidence: 83%
“…The writing group recommends that choice of therapy should always be discussed in full with every woman and be individualised for the patient, taking into account a woman's concerns and preferences , in accordance with the standard treatment guidelines. Nucleoside backbone combinations recommended by BHIVA for HIV in pregnancy include tenofovir DF/emtricitabine and abacavir/lamivudine.…”
Section: Current Issues In the Use Of Art In Pregnancy And Pregnanmentioning
confidence: 99%
“…Nucleoside backbone combinations recommended by BHIVA for HIV in pregnancy include tenofovir DF/emtricitabine and abacavir/lamivudine. Pregnant women may also want to consider zidovudine/lamivudine . Considerations for the backbone include side‐effect profile, frequency of dosing, interactions with the third agent, adverse outcome profiles and prior cART experience including a resistance profile where available.…”
Section: Current Issues In the Use Of Art In Pregnancy And Pregnanmentioning
confidence: 99%
“…For children, one high-quality review [65], one medium-quality review [41] and two lowquality reviews [68,73] contributed to the aggregation of findings. For adults, two high-quality reviews [62,65], four medium-quality reviews [43,55,61,67] and twenty low-quality reviews [44, 47, 48, 50-56, 58-68, 70-73] contributed to the findings for adherence to ART.…”
Section: Barriers and Facilitators To Adherence To Artmentioning
confidence: 99%